FIGURATIVE LANGUAGE USED IN THE SONG LYRIC OF ELLIE GOULDING ALBUM â€œBRIGHTEST BLUEâ€ - Mete, Aloysius Andelo; Putri, I Gusti Ayu Vina Widiadnya; Juniartha, I Wayan (LITERA : Jurnal Bahasa Dan Sastra, 2024)
The objectives of the study are to identify the types of figurative language and analyzed the meaning of the figurative language used in Ellie Gouldingâ€™s song lyrics. The data were analyzed based on the theory from Knickerbocker and Reninger (1963). Used to identify the types of figurative language and theory proposed by Leech (1974). The method used in collecting the data was observation method. The result show there are 5 types of figurative language used in the song lyrics of Ellie Gouldingâ€™s album â€œBrightest Blueâ€. They are; simile, metaphor, Personification, Synecdoche and Hyperbole. There were found 19 sentences identified using those seven types of figurative language such as: 10 of simile (47,61%), 1 of metaphor (4,76%), 1 metaphor (4,76%), 1 personification (4,76%), 3 of Synecdoche (14,28%), 1 of Metonymy (4,76%), 4 of Hyperbole (19,047%) 1 of Allusion (4,76). The result show there are two types of meaning used in the song lyrics of Ellie Gouldingâ€™s album â€œBrightest Blueâ€, such are; connotative meaning, conceptual meaning and affective meaning It can be in dictated that the dominant type of figurative language in the song lyrics is hyperbole. The meaning of figurative language is also stated clearly.